The relic of Perilous Falls - Arroyo, Raymond (Arroyo, Raymond. Will Wilder, 2016)
"A thrill-seeking twelve-year-old boy with a mysterious family heritage discovers ancient objects of rare power--and must protect them from the terrifying demons who will do anything to possess them"--